Offene Kommunikation bei Krebserkrankungen (PPmP - Psychotherapie · Psychosomatik · Medizinische Psychologie, 2017)
Meriggi F et al. Parents with cancer: Searching for the right balance between telling the truth and protecting children. Palliat Support Care 2017; 15: 88–97